2019
DOI: 10.14807/ijmp.v10i1.787
|View full text |Cite
|
Sign up to set email alerts
|

Work safety management applied to a lab used by a junior company of chemical engineering

Abstract: This article aims at the implementation of safety at work in the daily life of a Junior Company, which often uses laboratories for chemical analysis. To achieve the objective, initially a risk map was structured. Then, a business model was defined, adding safety factors through the methodology of Business Model Canvas. And finally, the application of the Balanced Scorecard, proposing objectives and operation’s indicators relating this specific junior company. When the analysis was done, the presence of hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Their knowledge and experience, especially in small and medium-sized enterprises, is the main factor determining the level of OSH in the company. Large enterprises, often operating within a corporation, have top-down procedures that greatly improve safety at work ( Chiroli et al, 2019 , Mansour, 2018 , Beardwood and Kainer, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their knowledge and experience, especially in small and medium-sized enterprises, is the main factor determining the level of OSH in the company. Large enterprises, often operating within a corporation, have top-down procedures that greatly improve safety at work ( Chiroli et al, 2019 , Mansour, 2018 , Beardwood and Kainer, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Education is a strong tool in the systematic construction and promotion of knowledge and skills in all fields, as well as in creating desired attitudes towards issues of occupational safety and health (OSH), including the environment, the safety of technical equipment, the optimization of working conditions, and first aid (Bail et al, 2019;Chiroli et al, 2019;Kozík and Bulla, 2013). "Teaching" AND "engineering" AND "first aid" 0 papers 6 papers 0 papers 0 papers 1 paper 0 papers "Teaching" AND "prehospital care" AND "engineering academics" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers "Prehospital care" AND "engineering course" AND "discipline" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers "Teaching" AND "prehospital care" AND "university students" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers "First aid" AND "engineering academics" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers "Discipline" AND "first aid" AND "university academics" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers "Primeiros socorros" AND "acadêmicos" AND "engenharia" 0 papers 0 papers 0 papers 0 papers 0 papers 0 papers…”
Section: Resultsmentioning
confidence: 99%
“…The European Agency for Safety and Health at Work has published an EU guide on workplace adaptation during the COVID-19 epidemic. As risk assessment is the starting point in occupational safety management [9,10], it is assumed that employers are required to verify the level of risk when there are any changes to the work process, even if they only affect workers' mental health. It is suggested that this additional risk assessment should also be based on current data on the prevalence of COVID-19 in the area where the company operates.…”
Section: Review Of the Subject Literaturementioning
confidence: 99%